“Maurice est si loin qu’on ne peut qu’en rêver”: le Paradis perdu de J.M.G. Le Clézio entre mythe et mémoire (Altre Modernità, 2012)
The theme of paradise or better the paradise lost, understood as the Garden of Eden where natural harmony, innocence and principles of liberty reigned, is developed by the writer J.M.G. Le Clézio with a certain obsession. Different within his work are the geographical points which from time to time adapt to represent this topos; but one in particular repeats consistently: it is the island of Mauritius. A curious relationship unites the author to this island – from which his parents and relatives were unjustly exiled – beginning from the typical Mauritian education he received, even though born and grown up in France. The feeling with which Le Clézio approaches the island, until today by the majority considered a paradise on Earth, differs indeed from the search of an exotic place (even though his novels do not miss descriptions of breathtaking landscapes and pure nature) and it identifies itself as a contemplation of the homeland – cradle to which he and his family remained bound despite the forced distance. Starting by detecting some factors that various Leclezian novels have in common, this article offers itself to bring to light an attempt of the author to regain through writing his own Mauritian paradise. A research which passes for Le Clézio as will be seen across a miscellanea of elements of a Biblical myth involved in the genesis of man with stories, memories, dreams and family hopes.
Keywords: “Le Clézio”; “Paradis terrestre”; “Ile Maurice”; “Mémoire familiale”; “Mythe Biblique”